HYBRID INTEGRATION OF EXPERT SYSTEMS INTO AVIATION LOGISTICS MANAGEMENT STRUCTURES - SYDORENKO, Oleh; LYSA, Nataliia (Computer systems and information technologies, 2026)
In this study authors considered the integration of expert systems into management of aviation logistics. The complexity of this integration is in the management structures and in the context of the operational complexity which is constantly increasing and the continuous supply of chain operations. It was determined that the existing systems and methods to make a decisions are not full sufficient with big data processing and do not taking into account the dynamic changes or does not fully smooth out the risk factors in aviation logistics. It was agreed that the traditional methods are not enough effective when the tasks are to process a big amount of data in conditions of dynamic changes. It was detected that the integration of expert systems which are able to simulate professional knowledge and operational expertise making a big impact on the decisions quality and reduces the human factor in critical operational time and provides adaptive and flexible planning. In this study authors are also analyze and compare several modern systems, such as NAVBLUE, Ramco Aviation Suite, Veronte Autopilot, ARTAS, FANS-1/A, TCAS II, RUN.S.A.F.E., SAREX, AIR Cargo handling System Assessment Model and Astrea UAV Integration Platform. The authors found that, regardless of the individual functional capabilities of each system, modern aviation expert systems are quite fragmented and do not have unified architectural approaches. This leads to the need to develop a hybrid integration model that will be focused on combining expert system cores with centralized logistics planning. In this article, the authors proposed new architectural and methodological approaches to building a modular, standardized architecture that unites distributed knowledge, synchronizes analytical processes, and provides unified integration into digital platforms such as ERP, MES, TMS. The practical meaning of this research is to find possible transformations of existing aviation logistics practices using unified hybrid decision support systems and in managing the design of future digital aviation infrastructures.